Phase transition thermal response gel based on ionic liquid / water binary solvent as well as preparation method and application of phase transition thermal response gel

By introducing ionic liquid/water binary solvents into the thermochromic hydrogel, a gel material with phase transition characteristics is formed, which solves the problems of poor cycle stability and anti-freeze properties, and achieves efficient thermochromic performance and rapidity Responsive, suitable for smart window applications.

CN119119356AActive Publication Date: 2024-12-13SUZHOU DONGBO MEDICAL EQUIPMENT CO LTD +1

Patent Information

Application Number
CN202411174696.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-07-24
Filing Date
2024-08-26
Publication Date
2024-12-13
Estimated Expiration
2044-08-26

AI Technical Summary

Technical Problem

The existing thermally discolored hydrogel smart window circulation stability is poor, and the network structure shrinkage performance attenuation and anti-freeze performance are poor, which limits its large-scale application.

Method used

The phase-transformation thermal response gel based on ionic liquid/water binary solvent is used to polymerize in water by polymerizing monomers, ionic liquids, initiators and accelerators to form a gel state that can be present at high temperatures and a sol state that is present at low temperatures. The material, which replaces traditional crosslinking agents, achieves rapid response and high cycle stability.

Benefits of technology

Achieve high visible light transmittance and solar light modulation rate, fast thermal response speed, and performance does not decay after 500 thermal discoloration cycles, overcoming the volume shrinkage and performance degradation of traditional hydrogels, providing excellent cycling stability and freezing resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119356A_ABST
    Figure CN119119356A_ABST
Patent Text Reader

Abstract

The invention discloses a phase transition thermal response gel based on an ionic liquid / water binary solvent, and a preparation method and application thereof. The phase transition thermal response gel system comprises an N-isopropylacrylamide (NIPAm) monomer, an initiator, an accelerator, an ionic liquid and water. NIPAm is used as a thermal response unit, the introduction of the ionic liquid replaces a common cross-linking agent for hydrogel polymerization, and the interaction of multiple hydrogen bonds and ions formed between the ionic liquid and a poly N-isopropylacrylamide (PNIPAm) chain endows the system with the characteristic of phase transition. The phase transition thermochromic intelligent window of the ionic liquid / water binary solvent prepared by the invention has the characteristics of high light transmittance, fast response, adjustable response temperature and good stability, and overcomes the defects that the traditional thermochromic hydrogel generates serious volume shrinkage after generating long-term thermochromic circulation and the thermochromic performance is reduced; and a certain technical support is provided for the application of the thermochromic intelligent window.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, and in particular to a phase-transition thermal response gel based on an ionic liquid / water binary solvent, and a preparation method and application thereof. Background Art

[0002] Windows are building components that are directly connected to the outside world. Especially in the hot summer, sunlight will enter the room through the poorly insulated glass, further exacerbating the increase in indoor temperature. People have to turn on air conditioners and other refrigeration equipment to cool down, which undoubtedly increases the energy consumption of the building. In order to reduce building energy consumption, smart windows came into being. Currently, the most studied smart window technologies focus on electrochromism (electrical response), photochromism (light response) and thermochromism (thermal response). Among them, thermochromism technology is considered to be the most cost-effective and easy-to-implement solution among the above-mentioned smart window technologies. It has outstanding advantages. As a passive color change strategy, it can autonomously adjust its transmittance by sensing the ambient temperature. For example, when the temperature is high (exceeding its critical response temperature), the smart glass becomes opaque and scatters the incident sunlight to block the entry of sunlight. When the temperature is low, it will return to transparency and allow as much sunlight as possible to enter. Compared with electrochromic smart windows, it does not consume any energy. Secondly, thermochromic smart windows are easy to prepare and do not require the complex preparation process of photochromic windows or the use of expensive conductive glass like electrochromic windows, which makes their production costs lower.

[0003] Traditional thermochromic materials, such as vanadium dioxide (VO2), have low optical contrast and solar modulation rate, slow response speed, and high thermal response temperature (~68°C), which seriously limit their large-scale application. Poly (N-isopropylacrylamide) (PNIPAm) hydrogel has attracted much attention due to its high optical contrast and solar modulation rate, but the three-dimensional cross-linked network structure of PNIPAm hydrogel will undergo irreversible shrinkage during long-term thermochromic cycles, resulting in the destruction of its structural uniformity and the decline of the thermochromic performance of the hydrogel. In addition, the high water content in the hydrogel also causes it to freeze under low temperature conditions such as winter, which damages the hydrogel network structure and performance.

[0004] Patent CN106188388A discloses a thermal / electrically responsive gel photochromic glass material, which is obtained by dissolving a thermally responsive monomer, an ionic liquid, a crosslinking agent, an initiator and a catalyst in water for polymerization. By modifying the polymer formed by the polymerization of the thermally responsive monomer and the crosslinking agent with an ionic liquid, a thermally and electrically responsive gel photochromic glass material can be formed, thereby increasing the responsiveness to changes in environmental conditions; improving the temperature controllability, stability and service life of the color-changing device.

[0005] Patent CN113512146A is a self-sensing hydrogel light-transmitting smart glass and its preparation method. The self-sensing hydrogel is composed of a polymer monomer, a surfactant, an enhancer, a corresponding initiator, a cross-linking agent, (accelerator), and a salt solution. The present invention uses the surfactant in the hydrogel as a response unit, which will spontaneously generate micelles with cations in the salt solution in the gel network. The micelles will change in particle size under the action of heat, electricity, and pH, and the macroscopic manifestation is the change in the transmittance of the prepared gel. When the hydrogel is in a solution state, it is injected into the laminated glass and sealed. After it is gelled in situ, a self-sensing multi-responsive light-transmitting smart glass can be obtained. Summary of the invention

[0006] Aiming at a series of problems in the prior art such as poor cycle stability, attenuation of network structure shrinkage performance and poor antifreeze performance of thermochromic hydrogel smart windows. The present application proposes a phase-change thermoresponsive gel based on ionic liquid / water binary solvent and its preparation method and application. The prepared phase-change thermoresponsive gel based on ionic liquid / water binary solvent exhibits excellent cycle stability and thermochromic properties including high light transmittance and solar light modulation rate, fast thermal response speed, etc. The introduction of ionic liquid replaces the cross-linking agent required by traditional gel and gives the system the characteristics of phase transition, so that it presents a sol state (liquid state) below the critical transition temperature and a gel state (solid state) at high temperature, so that even if the system has a volume shrinkage problem, it can recover at a low temperature, thereby improving its cycle stability.

[0007] A phase-transition thermoresponsive gel based on an ionic liquid / water binary solvent, which is obtained by dissolving a polymerization monomer, an ionic liquid, an initiator and an accelerator in water for polymerization;

[0008] The polymerizable monomer is N-isopropylacrylamide, and the concentration of the polymerizable monomer is 8.6 wt% to 9.5 wt%. The polymerizable monomer can also be a copolymer of acrylamide or acrylic acid and N-isopropylacrylamide.

[0009] The above-mentioned ionic liquid is one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium methanesulfonate, 1-butyl-3-methylimidazolium nitrate, and 1-hexyl-3-methylimidazolium chloride. The concentration of the above-mentioned ionic liquid is 0.8wt% to 8.5wt%. If the concentration of the ionic liquid is too low, PNIPAm will shrink at high temperature, and it will take a long time for the ionic liquid / water binary solvent to dissolve the shrunken PNIPAm, and the switching between transparent and opaque states, that is, the thermal response speed will be affected. If the ionic liquid is too high, the critical transition temperature of the gel will be further reduced, and the practicality will be reduced. Therefore, by limiting the concentration of the ionic liquid, the response temperature can be adjusted.

[0010] The initiator is one of ammonium persulfate or potassium persulfate. The concentration of the initiator is 0.8wt% to 1.6wt%;

[0011] The accelerator is N,N,N',N'-tetramethylethylenediamine. The volume concentration of the accelerator is 0.1% to 0.3%. If the volume concentration of the accelerator exceeds 0.3%, the polymerization rate will only be further increased.

[0012] A method for preparing a phase transition thermal response gel based on an ionic liquid / water binary solvent comprises the following steps:

[0013] (1) dissolving the polymerization monomer, initiator, and ionic liquid in water, and performing magnetic stirring under ice bath conditions to accelerate dissolution;

[0014] (2) deoxygenating the solution obtained in step (1);

[0015] (3) adding an accelerator to the solution obtained in step (2), stirring the mixture evenly and then allowing it to stand to obtain a phase transition thermally responsive gel material of an ionic liquid / water binary solvent.

[0016] In the above step (1), the temperature of the ice bath is 0-10°C, and the stirring time is 10-30 minutes. In the above step (2), the deoxygenation operation is specifically to introduce nitrogen into the solution; and the time of introducing nitrogen is 10-30 minutes.

[0017] The phase-change thermal response gel based on ionic liquid / water binary solvent can be used as a thermochromic material. The adjustable response temperature range of the thermochromic material is 32.5°C to 25°C. The thermochromic material is a transparent liquid at low temperatures and a white opaque solid at high temperatures.

[0018] Different ionic liquid contents will result in different color change temperatures of the thermochromic smart window, which can be adjusted according to actual needs.

[0019] Preferably, it can be used to make thermochromic smart windows, specifically, the solution obtained in step (3) is dripped into a laminated glass mold, and after standing for a period of time, a thermochromic smart window containing a phase transition thermal response gel material of an ionic liquid / water binary solvent is obtained.

[0020] The glass mold includes parallel stacked glasses, and a cavity is formed between the glasses. Sealant is applied around the glass cavity. The thickness of the glass cavity is determined by the spacer strips, and the thickness is 0.5 to 5 mm. If the thickness is too thin, although it is not transparent at high temperatures, the transmittance to sunlight is less than 1%, which can basically achieve full blocking of sunlight; but if it is too thin, it will not block sunlight enough at high temperatures; if the thickness exceeds 5 mm, firstly, too much thermal response gel will be consumed, and secondly, at low temperatures (transparent state), its transmittance in the visible light range may be less than 90%, because even if it is too thick, the incident sunlight will be lost when passing through the smart window. In addition, if the thickness is too thin, the response speed will be faster, and if it is too thick, the response speed will be reduced, because temperature conduction also takes a certain amount of time.

[0021] The phase transition thermoresponsive gel of the ionic liquid / water binary solvent of the present invention uses N-isopropylacrylamide as a monomer in the system. After the initiator is added, NIPAm starts a free radical polymerization reaction. The introduction of the ionic liquid can change the solubility of NIPAm in the solvent, and can interact with the PNIPAm chain through ion-dipole interaction and van der Waals force, changing the interchain interaction of PNIPAm, thereby giving it the characteristics of phase transition. When the critical response temperature is above, the interaction between the PNIPAm chains is enhanced, and a conformational transition (chain conformation to spherical conformation, refer to Figure 1 ), forming scattering centers, thereby blocking the incident sunlight; when the ambient temperature is below the critical temperature, the interaction between PNIPAm chains is weak, the system appears to be a flowing sol state, transparent, and allows incident sunlight to enter.

[0022] Compared with the prior art, this application has the following advantages:

[0023] (1) The system uses N-isopropylacrylamide as a monomer, and ionic liquid replaces the traditional cross-linking agent. The ionic liquid can interact with the PNIPAm molecular chain through ion-dipole interaction and van der Waals force, changing the interchain interaction of PNIPAm, so that it presents different states at high / low temperatures. When the critical response temperature is exceeded, it presents a gel state (white and opaque); at low temperatures, it returns to a sol state (colorless and transparent).

[0024] (2) The prepared phase-change thermoresponsive gel exhibits high thermochromic properties, including high visible light transmittance and solar light modulation rate, and fast thermal response speed (switching between transparent / opaque states can be completed in 10s).

[0025] (3) The phase transition characteristics endow the thermochromic hydrogel with excellent cyclic stability. After 500 thermochromic cycles, its performance does not show obvious attenuation. This is due to the phase transition characteristics of the system. Even if the gel network of the system shrinks after multiple cycles, the system will return to the sol state after the temperature returns to low temperature.

[0026] (4) The prepared phase-change thermal response gel precursor solution can be directly poured into the laminated glass. After standing for a period of time, a thermochromic smart window can be obtained. In addition, the phase-change gel can be recycled. When it is cooled below the critical response temperature and the system is converted into a sol state, it can be poured out from the laminated glass and reused. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 Schematic diagram of the color change mechanism of the phase transition thermoresponsive gel of ionic liquid / water binary solvent;

[0028] Figure 2 This is a graph showing the test results of the UV-visible-near infrared transmittance of the smart window made of the phase-transition thermal response gel of the ionic liquid / water binary solvent in Example 2 at different temperatures;

[0029] Figure 3 The transmittance images of the phase transition thermal response gel smart window (10 cm×10 cm) of the ionic liquid / water binary solvent of Example 2 at low temperature 20°C and high temperature 40°C;

[0030] Figure 4 This is a photo of a large-sized thermochromic window (30 cm×30 cm) in Example 2 that turns white when touched by hand in an outdoor environment;

[0031] Figure 5 These are photos of the phase transition thermoresponsive gel of the ionic liquid / water binary solvent of Example 2 at low temperature of 20°C and high temperature of 40°C;

[0032] Figure 6 This is the phase transition process of the thermoresponsive gel of the phase transition of the ionic liquid / water binary solvent of Example 2 when injected into 35°C water;

[0033] Figure 7 The photographs are of Example 2 (ionic liquid modification) and Comparative Example 1 after 200 cycles of thermochromic cycles (20 / 40°C);

[0034] Figure 8 Thermochromic visible light transmittance of Example 2 within 200 cycles (tested once every 10 thermochromic cycles). DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] The critical response temperature in the following embodiments or comparative examples is measured by the following method: prepare water of different temperatures, immerse the glass bottle containing the gel in the water, and identify the temperature as the critical response temperature after it turns obviously white.

[0037] Embodiment 1:

[0038] 1.05g N-isopropylacrylamide monomer, 0.1g ammonium persulfate, 0.1g 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid were dissolved in 10mL deionized water, and magnetic stirring was carried out for 20min under 0℃ ice bath to ensure that each component was completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into a glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and thermochromic smart windows were obtained after standing for 5h. The critical response temperature is 32℃, the transmittance is 96.7% (at 550nm) at 20℃, and the transmittance is 1.8% (at 550nm) at 40℃.

[0039] Embodiment 2:

[0040] 1.05g N-isopropylacrylamide monomer, 0.1g ammonium persulfate, 0.5g 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid were dissolved in 10mL deionized water, and magnetically stirred for 20min in an ice bath at 0℃ to ensure that all components were completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into a glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and thermochromic smart windows were obtained after standing for 5h. The critical response temperature is 30℃, the transmittance is 97.2% (at 550nm) at 20℃, and the transmittance is 1.2% (at 550nm) at 40℃. Reference Figure 2-Figure 6 , Figure 8 .

[0041] Embodiment 3:

[0042] 1.05g N-isopropylacrylamide monomer, 0.1g ammonium persulfate, 1.0g 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid were dissolved in 10mL deionized water, and magnetic stirring was carried out for 20min under 0℃ ice bath to ensure that each component was completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 20 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into a glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 2mm), and thermochromic smart windows were obtained after standing for 3h. The critical response temperature is 28℃, the transmittance is 94.8% (at 550nm) at 20℃, and the transmittance is 0.5% (at 550nm) at 40℃.

[0043] Embodiment 4:

[0044] 1.05g N-isopropylacrylamide monomer, 0.1g ammonium persulfate, 0.5g 1-butyl-3-methylimidazolium chloride, dissolved in 10mL deionized water, magnetically stirred for 20min under 0℃ ice bath to ensure that all components are completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into a glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and thermochromic smart windows were obtained after standing for 5h. The critical response temperature is 28.5℃, the transmittance is 95.3% (at 550nm) at 20℃, and the transmittance is 1.4% (at 550nm) at 40℃.

[0045] Embodiment 5:

[0046] 1.05g N-isopropylacrylamide monomer, 0.2g ammonium persulfate, 0.5g 1-butyl-3-methylimidazole methanesulfonate, dissolved in 10mL deionized water, magnetically stirred for 20min under 0℃ ice bath to ensure that all components are completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into a glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and thermochromic smart windows were obtained after standing for 5h. The critical response temperature is 25℃, the transmittance is 82.5% (at 550nm) at 20℃, and the transmittance is 0.8% (at 550nm) at 40℃.

[0047] Comparative Example 1:

[0048] 1.05g N-isopropylacrylamide monomer, 0.2g ammonium persulfate, 0.012g N,N'-methylenebisacrylamide were dissolved in 10mL deionized water, and magnetic stirring was carried out for 20min under 0℃ ice bath to ensure that all components were completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into the glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and the thermochromic smart window was obtained after standing for 5h. The thermochromic PNIPAm hydrogel prepared by this method has a critical response temperature of 32.5℃, a transmittance of 94.8% (at 550nm) at 20℃, and a transmittance of 1.8% (at 550nm) at 40℃. It is worth noting that the stability of the PNIPAm hydrogel-based smart window is poor. After a long period of thermochromic cycling, the PNIPAm hydrogel in the glass interlayer will shrink in volume and its performance will decay. Figure 7 shown.

[0049] Comparative Example 2:

[0050] 1.05g N-isopropylacrylamide monomer and 0.2g ammonium persulfate were dissolved in 10mL deionized water, and magnetically stirred for 20min under 0℃ ice bath conditions to ensure that all components were completely dissolved; nitrogen was introduced for 10min to remove the dissolved oxygen in the mixed solution, and 10 microliters of N,N,N',N'-tetramethylethylenediamine was added, and the mixed solution was poured into the glass cavity (glass size: 10cm×10cm, thickness 1mm; glass cavity spacing 1mm), and the thermochromic smart window was obtained after standing for 5h. Its initial state is sol state (flowable), the critical response temperature is 32.5℃, and the transmittance is 93.4% (at 550nm) at 20℃. However, after heating at 40℃, the obtained PNIPAm sol state will undergo phase separation, and PNIPAm will precipitate free water in the network, but it is difficult to return to the initial sol state. That is, without the assistance of ionic liquid, it cannot be transformed from the high-temperature gel state back to the sol state, and the thermochromic function is lost.

[0051] Comparative Example 3

[0052] 1.05 g of N-isopropylacrylamide monomer, 0.1 g of ammonium persulfate, and 0.5 g of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid were dissolved in 10 mL of deionized water, and magnetically stirred for 20 min under 0°C ice bath conditions to ensure that all components were completely dissolved; nitrogen gas was introduced for 10 min to remove the dissolved oxygen in the mixed solution, and the mixed solution was poured into a glass cavity (glass size: 10 cm×10 cm, thickness 1 mm; glass cavity spacing 1 mm). After standing for 5 h, no thermochromic smart window could be obtained, that is, without the assistance of an accelerator, the precursor solution could not be transformed into a sol state, and it remained transparent at 40°C.

[0053] The present invention uses NIPAm as a thermal response unit, and the introduction of ionic liquid replaces the commonly used cross-linking agent for hydrogel polymerization. The multiple hydrogen bonds and ionic interactions formed between the ionic liquid and the PNIPAm (poly N-isopropylacrylamide (PNIPAm)) chain give the system the characteristics of phase transition, that is, it presents a sol state at low temperature, and it presents a gel state after exceeding the critical response temperature, and the gel transmittance varies greatly during the phase transition process. The thermochromic gel precursor solution is injected into the laminated glass and sealed to obtain a thermochromic smart window. At low temperatures, the system presents a sol state (transparent), thereby allowing incident light to enter; and when the environment exceeds the critical response temperature of the gel, the system presents a gel state (opaque). The phase transition thermochromic smart window of the ionic liquid / water binary solvent prepared by the present invention has the characteristics of high light transmittance, fast response, adjustable response temperature, and good stability, and it overcomes the defects of traditional thermochromic hydrogels that serious volume shrinkage and decreased thermochromic performance occur after long-term thermochromic cycles, and has good application prospects in thermochromic smart windows.

[0054] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A phase transition thermoresponsive gel based on an ionic liquid / water binary solvent, characterized in that: It is obtained by dissolving polymerization monomers, ionic liquids, initiators and accelerators in water for polymerization; The concentration of the polymerizable monomer is 8.6 wt% to 9.5 wt%; The concentration of the ionic liquid is 0.8wt% to 8.5wt%; The initiator concentration is 0.8wt% to 1.6wt%; The volume concentration of the accelerator is 0.1% to 0.3%.

2. The phase transition thermoresponsive gel based on ionic liquid / water binary solvent according to claim 1, characterized in that: The polymerizable monomer is N-isopropylacrylamide.

3. The phase transition thermoresponsive gel based on ionic liquid / water binary solvent according to claim 1, characterized in that: The ionic liquid is one of 1-butyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium trifluoromethanesulfonate, 1-butyl-3-methylimidazolium methanesulfonate, 1-butyl-3-methylimidazolium nitrate, and 1-hexyl-3-methylimidazolium chloride.

4. The phase transition thermoresponsive gel based on ionic liquid / water binary solvent according to claim 1, characterized in that: The initiator is one of ammonium persulfate or potassium persulfate.

5. The phase transition thermoresponsive gel based on ionic liquid / water binary solvent according to claim 1, characterized in that: The accelerator is N,N,N',N'-tetramethylethylenediamine.

6. A method for preparing a phase transition thermal response gel based on an ionic liquid / water binary solvent according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) dissolving the polymerization monomer, initiator, and ionic liquid in water, and performing magnetic stirring under ice bath conditions to accelerate dissolution; (2) deoxygenating the solution obtained in step (1); (3) adding an accelerator to the solution obtained in step (2), stirring the mixture evenly and then allowing it to stand to obtain a phase transition thermally responsive gel material of an ionic liquid / water binary solvent.

7. The preparation method according to claim 6, characterized in that: The ice bath temperature in step (1) is 0-10° C., and the stirring time is 10-30 min.

8. The preparation method according to claim 6, characterized in that: The deoxygenation operation in step (2) is specifically to introduce nitrogen into the solution; the time for introducing nitrogen is 10 to 30 minutes.

9. Use of the phase-transition thermoresponsive gel based on ionic liquid / water binary solvent according to any one of claims 1 to 5 as a thermochromic material.

10. A thermochromic smart window, characterized in that: The thermochromic material is dripped into a laminated glass mold and left to stand for a period of time to obtain a thermochromic smart window; the thermochromic material is the thermochromic material according to claim 9.

Citation Information

Patent Citations

  • Heat / electric responding gel color changing glass material

    CN106188388A

  • Method for regulating and controlling modulus change range of thermal response ionic liquid gel and thermal response ionic liquid gel

    CN113501907A

Cited By

  • Ion thermoelectric material and preparation method and application thereof

    CN120461982A